Pengaruh Etika Profesi Terhadap Pertimbangan Tingkat Materialitas Dalam Pemeriksaan Laporan Keuangan Pada PT. Bhakti Sehat Husada Medan - Rangkuti, M Ihsan; Arnita, Vina (Economics, Business and Management Science Journal, 2024)
This research is titled "The Influence of Professional Ethics on the Consideration of Materiality in Financial Statement Examination at PT Bhakti Sehat Husada Medan". It employs a quantitative method aiming to determine the impact of professional ethics, using a sample of 30 individuals. The sample in this study consists of employees registered as respondents in the company PT Bhakti Sehat Husada Medan. Data collection was conducted through questionnaire distribution and documentation of the questionnaire results. In the analysis process, various tests were employed, including normality test, Multicollinearity test, Heteroscedasticity test, multiple linear regression test, R² test, as well as the F test (simultaneous) and t test (partial). The test results indicated that partially there is no effect between professional ethics (X1) and the materiality level (Y) in the company PT Bhakti Sehat Husada.